2016
DOI: 10.1007/s00423-016-1397-0
|View full text |Cite
|
Sign up to set email alerts
|

Linear compared to circular stapler anastomosis in laparoscopic Roux-en-Y gastric bypass leads to comparable weight loss with fewer complications: a matched pair study

Abstract: Linear stapler anastomosis in LRYGB compared to circular anastomosis leads to equal weight loss and less strictures. The lower rate of internal hernias in linear stapler anastomosis was not significantly different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…However, no studies have evaluated QoL following totally laparoscopic surgery. Schneider et al[ 36 ] reported that the diameter of the anastomotic stoma obtained using the linear stapler was significantly larger than that achieved with the circular stapler, which benefits the passage of food. At 6 mo post-surgery, we found that symptoms of dysphagia were better in group T, especially in terms of eating solid food.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have evaluated QoL following totally laparoscopic surgery. Schneider et al[ 36 ] reported that the diameter of the anastomotic stoma obtained using the linear stapler was significantly larger than that achieved with the circular stapler, which benefits the passage of food. At 6 mo post-surgery, we found that symptoms of dysphagia were better in group T, especially in terms of eating solid food.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, circular staplers may be used to create the gastrojejunostomy anastomosis as an alternative to the staplers of interest under study, which introduces potential for use of another device in an important step of the LRY. There are presently mixed data on whether circular staplers increase the risk of complications in in LRY 24,25 ; however, if this technique correlates with use of powered vs manual staplers, it is possible that it could be a confounding factor for a number of the study outcomes-particularly costs arising from use of a second device. Thus, another sensitivity analysis was performed in which circular stapler use was included as a covariate in the multivariable models for the sub-group of patients undergoing LRY.…”
Section: Sub-group and Sensitivity Analysesmentioning
confidence: 99%
“…In 2009, we changed from the circular to the linear stapling LRYGB technique. Our technique has been described in detail previously [20]. In brief, the GE between the gastric pouch and the alimentary limb is created by two-thirds of the length of a 45-mm linear stapler magazine.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In the original version of the linear stapled LRYGB technique described by Hans Lönroth, the mesenteric defects were not closed, but the omentum was routinely split in the vertical direction to facilitate a tension free anastomosis between AL and the pouch [7]. As a consequence of the evidence provided by Aghajani et al and Stenberg et al, in 2016, we started closing mesenteric defects as part of our antecolic linear LRYGB technique [13,17,20]. However, though the rate of Petersen hernias was low in our previously published results, the new closure technique could cause obstruction of the transverse colon or bleeding at the transverse mesocolon.…”
Section: Introductionmentioning
confidence: 99%